REDE DE ASSISTÊNCIA INTEGRAL À SAÚDE DO IDOSO: EXPERIÊNCIA DE ENFERMEIROS GERENTES NA ATENÇÃO PRIMÁRIA - Nádia Placideli Ramos; Silvia Cristina Mangini Bocchi (Universidade Federal do Paraná, 2022)
Objective: to understand the conception of the comprehensive care network for older adults according to the experiences of nurse-managers working in Primary Health Care services. Methods: a qualitative research study conducted in 2019 in a number of host municipalities from five health regions of the state of São Paulo, Brazil. The interviews were audio-recorded, transcribed and analyzed according to the Grounded Theory, with theoretical saturation from the fifth interview. Results: three sub-processes emerged, namely: recognizing potential for the constitution of a comprehensive care network for older adults in the context of the public health system; getting discouraged for not visualizing the Care Network for Older Adults, given the organizational and cultural challenges to strengthen Primary Health Care; and discouragement to mobilize towards the constitution of the comprehensive care network for older adults. Final Considerations: this study contributes for the teams working in the Primary Health Care services to reassess their health practices, seeking to advance in the constitution of the comprehensive care network for older adults.